Cloning and Characterization of a Novel Carotenoid Cleavage Dioxygenase 1 from Helianthus annuus. Issue 1 (6th December 2021) - Qi, Zhipeng; Tong, Xinyi; Bu, Su; Pei, Jianjun; Zhao, Linguo
Abstract: Natural β‐ionone, a high‐value flavoring agent, has been widely applied in the food, cosmetics, and perfume industry. However, attempts to overproduce β‐ionone in microorganisms have been limited by the efficiency of carotenoid cleavage dioxygenases (CCDs), which catalyzes β‐carotene in the biosynthesis pathway. In order to obtain CCD genes responsible for the specific cleavage of carotenoids generating β‐ionone, a novel carotenoid cleavage dioxygenase 1 from Helianthus annuus was cloned and overexpressed in Escherichia coli BL21(DE3). The recombinant CCD was able to cleave a variety of carotenoids at the 9, 10 (9′, 10′) sites to produce C13 products in vitro, including β‐ionone, pseudoionone, 3‐hydroxy‐4‐oxo‐β‐ionone, 3‐hydroxy‐β‐ionone, and 3‐hydroxy‐α‐ionone, which vary depending on the carotenoid substrates. In comparison with lycopene and zeaxanthin, HaCCD1 also showed the high specificity for β‐carotene to cleave the 9, 10 (9′, 10′) double bond to produce β‐ionone in E. coli accumulating carotenoids. Finally, the expression of HaCCD1 in E. coli was optimized, and biochemical characterizations were further clarified. The optimal activity of HaCCD1 was at pH 8.8 and 50 °C. The V max for β‐apo‐8′‐carotenal was 10.14 U/mg, while the K m was 0.32 mM. Collectively, our study provides a valuable enzyme for the synthesis of natural β‐ionone by biotransformation and synthetic biology platform. Abstract :